Stability of Oil-in-Water Emulsions with Sunflower (Helianthus annuus L.) and Chia (Salvia hispanica L.) By-Products - Guiotto, Estefanía Nancy (2015)
Emulsifiers and stabilizers play an important role in emulsion stability. Optical characterization and droplet size distribution of oil-in-water emulsions formulated with different types and concentrations of modified sunflower lecithin [phosphatidylcholine (PC) enriched lecithin and deoiled sunflower lecithin], with or without chia mucilage (0.75 % wt/wt), have been evaluated as a function of storage time at 4 ± 1 °C. Emulsions with PC-enriched lecithin (without chia mucilage) exhibited the highest stability at the different concentrations because of the high PC/phosphatidylethanolamine ratio in comparison to Control lecithin. The addition of 0.75 % wt/wt mucilage contributed to obtain stable emulsions for all type and concentrations of emulsifiers studied, mainly with PC-enriched lecithin due to the reduction of the mobility of oil particles by the formation of a tridimensional network.